Invasive blue mussels threaten regional scale genetic diversity in mainland and remote offshore locations: the need for baseline data and enhanced protection in the Southern Ocean. (22nd June 2016) - Gardner, Jonathan P. A.; Zbawicka, Małgorzata; Westfall, Kristen M.; Wenne, Roman
Abstract: Human‐mediated biological transfers of species have substantially modified many ecosystems with profound environmental and economic consequences. However, in many cases, invasion events are very hard to identify because of the absence of an appropriate baseline of information for receiving sites/regions. In this study, use of high‐resolution genetic markers (single nucleotide polymorphisms – SNPs) highlights the threat of introduced Northern Hemisphere blue mussels ( Mytilus galloprovincialis ) at a regional scale to Southern Hemisphere lineages of blue mussels via hybridization and introgression. Analysis of a multispecies SNP dataset reveals hotspots of invasive Northern Hemisphere blue mussels in some mainland New Zealand locations, as well as the existence of unique native lineages of blue mussels on remote oceanic islands in the Southern Ocean that are now threatened by invasive mussels. Samples collected from an oil rig that has moved between South Africa, Australia, and New Zealand were identified as invasive Northern Hemisphere mussels, revealing the relative ease with which such non‐native species may be moved from region to region. In combination, our results highlight the existence of unique lineages of mussels (and by extension, presumably of other taxa) on remote offshore islands in the Southern Ocean, the need for more baseline data to help identify bioinvasion events, the ongoing threat of hybridization and introgression posed by invasive species, and the need for greater protection of some of the world's last great remote areas.